Live high - train low in the heat: An efficient new training model? - Buchheit, M.; Racinais, S.; Bilsborough, J.; Hocking, J.; Mendez-Villanueva, A.; Bourdon, P.; Voss, S.; Livingston, S.; Cordy, J.; Coutts, A. J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: The purpose of the present study was to examine performance and physiological responses to a 14-day pre-season training camp combining heat exposure and hypoxia during sleeping (hypoxia) and training (hypoxia and heat) in 17 professional Australian Rules Football (ARF) players (22±2 yr). Methods: Players participated in 10 outdoor ARF-specific skills (32±1°C, 39±5% RH, total=11.5 h) and 8 indoor strength (23±1°C, 57±2%) sessions. In addition, they slept (12 nights) and cycled indoors (22±1°C, 58±2%, 7 "interval cycling" sessions, total 4.3 h) in either normal air (NORM, n=8) or normobaric hypoxia (14 ±1 h/day, 2500-3000m, HYP, n=9). The camp was followed by a week of unloaded training (4 skills [.29°C, .55%] and 7 strength [indoor] sessions, 10.5 h) and 10 d of unsupervised training. Training load was monitored using session-RPE x duration. Players performed the Yo-Yo Intermittent Recovery level 2 (Yo-YoIR2) in temperate conditions (23±1°C, 57±2%, normal air) at pre, post and 3 weeks post camp. Hemoglobin mass (Hbmass) and blood volume (BV) were measured at similar time points. Results: There was no clear difference in total training load between both groups during the camp (9786 ± 286 vs. 9904 ± 200 A.U. for HYP vs. NORM, respectively, -1% 90%CL (-3;1)) and the following weeks. Both groups showed very large improvements in Yo-YoIR2 post camp (+44% (38;50), ES = +2.3), with no between-group differences in the changes (-1%(-9;9) for HYP vs. NORM). Three weeks post camp, there was a possibly better Yo-YoIR2 performance maintenance in HYP (+6%(-2;15) for HYP vs. NORM). In HYP, Hbmass was likely (+3%(1;5), ES = 0.3) and very likely (+6%(2;10), ES = 0.7) increased post camp and 3 weeks after, respectively. Conversely, Hbmass did not change in NORM (0%(0;0) post camp). Post camp, both groups showed a likely (HYP, +4%(0;7), ES = 0.5) and very likely (NORM, +5%(2;9), ES = 0.8) increase in BV. Three weeks after, BV was very likely further increased in HYP (+7%(3;11) compared with pre-camp, ES = 1.3), while it tended to return to baseline in NORM (+2%(-5;9), difference rated as unclear). Discussion: Large increases in BV and high-intensity, intermittent running performance were observed after only 2 weeks using the present training model, with no additional benefit of hypoxic exposure at this time. However, only players that were exposed to hypoxia maintained their physical performance 3 weeks post camp, which was associated with an increased Hbmass and BV. While heat exposure is likely to account for rapid and important (but transient) changes, hypoxic exposure may enable more consistent (but delayed) effects. In conclusion, in addition to the well-known heat and/or altitude acclimation effects, the combination of heat and hypoxic exposure during sleeping/training times might offer a promising "conditioning cocktail" in team sports.